Between Representation and Eternity: The Archaeology of Praying in Late Medieval and Post-Medieval times. (February 2016) - Atzbach, Rainer
Abstract : This paper seeks to explore how prayer and praying practice are reflected in archaeological sources. Apart from objects directly involved in the personal act of praying, such as rosaries and praying books, churches and religious foundations played a major role in the medieval system of intercession. At death, an individual's corpse and burial primarily reflect the social act of representation during the funeral. The position of the arms, which have incorrectly been used as a chronological tool in Scandinavia, may indicate an evolution from a more collective act of prayer up to the eleventh century AD to a more individual way of praying in the late and post-medieval periods.